Partisipasi Dalam Beladiri Karate dan Agresifitas Anak Di Institut Karate-Do Indonesia (INKAI) - Mudrikah Ahmad; Rachmy Diana (UIN Sunan Kalijaga, 2013)
ABSTRACT The aim of this research was to found out the correlation between karate martial art participation and aggression on children karatekas. The proposed hypothesis in this research was negative correlation between karate martial art participation and aggression on children karatekas. The population in this research were children karatekas in INKAI DIY and the sample was 53 karatekas. The data were collected using karate martial art participation scale andaggression scale. Data analyzed with Pearson’s Product Moment correlation. The results showed that there was negative significant correlation between karate martial art participation and aggression on children karatekas, with r = - 0,535, p = 0,00 (p